Mangrove (Rhizophora sp.) Fruit Extract Inhibits Tumor Growth Factor (TGF)-β1 Expression in High Cholesterol Diet-Fed Rats: Ekstrak Buah Bakau (Rhizophora sp.) Menghambat Ekspresi Tumor Growth Factor(TGF)-β1 pada Tikus yang Mendapat Diet Tinggi Kolesterol - Hamidy, Muhammad Yulis; Masdar, Huriatul; Winarto, Winarto (Universitas Tadulako, 2021)
Background: Atherosclerosis is a major finding in cardiovascular disease. One of the pro-fibrotic cytokines that play an important role in the atherosclerosis process is Tumor Growth Factor (TGF)-β1, where the presence of high TGF-β1 secretion due to hypercholesterolemia will trigger excessive collagen matrix formation. Objective: To analyze Rhizophora sp fruit extract effect on TGF-β1 expression in high cholesterol diet-fed rats. Material and Methods: Eighteen 10-week-old rats weighing 150-200 g were used in this study. These animals were grouped into 3 groups, each consisting of 6 rats. Group A (normal control) is a group of rats that received a normal diet. Group B (atherogenic control) received a diet that induces atherosclerosis (atherogenic diet). This diet contains 2% cholesterol, 5% goat fat, 0.2% cholic acid and standard diet up to 100%. Atherogenic diet was given for 3 days, and on the first day this group also received vitamin D3 700,000 IU/kg. Group C (treated), apart from receiving an atherogenic diet, was also given Rhizophora sp fruit extract 500 mg/kg body weight. The Rhizophora sp fruit extract effect on TGF-β1 expression was evaluated by immunohistochemical procedure. The area of ​​the expression is calculated using the ImageJ. Results: The results of this study indicate that the expression of TGF-β1 is higher in the group receiving the atherogenic diet than the normal control group (17.3 vs. 8.9; P=0.000). Rhizophora sp fruit extract reduced this expression remarkably (17.3 vs. 11.4; P=0.001). Conclusion: Rhizophora sp fruit extract inhibits the the expression of TGF-β1 in high cholesterol diet-fed rats.